The Influence of Service Quality and Price Perception on Customer Loyalty: The Mediating Role of Customer Satisfaction in Ride-Hailing Service - Kia Hui Gan; Wei Chien Ng; Meenu Baliyan; Leena Zhee Keen Kee; Wai Voon Li; Shuo Li; Yiyang Liu; Visitra Dewangga Apriyanto; Kushagra Verma; Daisy Mui Hung Kee (International Journal of Applied Business and International Management, 2025)
The rapid growth of ride-hailing services in Southeast Asia has intensified competition, making customer loyalty a critical concern for platforms such as GrabCar. This study examines the effects of service quality and price perception on customer loyalty and investigates the mediating role of customer satisfaction among GrabCar users. A quantitative approach was applied using survey data collected from 150 users in Malaysia, Indonesia, and India through an online questionnaire. The data were analyzed using multiple regression and regression-based mediation analysis. The results indicate that service quality (? = 0.385, p 0.001) and price perception (? = 0.447, p 0.001) significantly influence customer satisfaction, explaining 78.1% of its variance (R² = 0.781). Customer satisfaction has the strongest positive effect on customer loyalty (? = 0.581, p 0.001), while price perception also directly affects loyalty (? = 0.234, p 0.001). In contrast, service quality does not have a significant direct effect on customer loyalty. The findings confirm that customer satisfaction fully mediates the service quality–loyalty relationship and partially mediates the price perception–loyalty relationship, highlighting satisfaction as the key driver of loyalty in ride-hailing services.